2001
DOI: 10.1080/03079450020023177
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid A amyloidosis in non-infected and avian leukosis virus-C persistently infected inbred ducks

Abstract: The breeding history of the first inbred strain of Khaki Campbell ducks is presented. The genetic homogeneity of this strain was tested on the basis of serum amyloid A (SAA) polymorphism and it was established that it harbours only the SAA allele A, which is expressed in liver, lung and bursa of Fabricius tissues. Pathogenic changes in control and avian leukosis virus-C (ALV-C) persistently infected ducks were evaluated during the period spanning 1 to 10 months after hatching. In both groups, AA amyloidosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…ALV-C has cytopathogenicity in cultured DF-1 cells (Himly et al, 1998). In recent years, ALV-C has often been used as a comparative system for establishing pathways leading to immunodeficiency syndrome in both homologous and heterologous hosts (Stepanets et al, 2001(Stepanets et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…ALV-C has cytopathogenicity in cultured DF-1 cells (Himly et al, 1998). In recent years, ALV-C has often been used as a comparative system for establishing pathways leading to immunodeficiency syndrome in both homologous and heterologous hosts (Stepanets et al, 2001(Stepanets et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…North American and Asian duck populations share wintering grounds, and at least two reports indicate the presence of ALV-J in ducks and partridges (17,18). Avian leukosis viruses of other subgroups can infect ducks and establish persistent infections in these heterologous hosts (38,39). On the other hand, we reported that NHE1 receptors of duck species are restrictive, and in vitro infection of duck embryo fibroblasts with ALV-J was inefficient (21).…”
Section: Discussionmentioning
confidence: 79%
“…(For virus strains, see Table 2.) Viruses were grown on the chicken embryo fibroblast cell line DF-1 (Himly et al, 1998) except for subgroup C viruses, which were propagated on duck embryo fibroblasts (isolated from inbred Khaki Campbell ducks of the D/ABDE phenotype from the breeding colony of the Institute of Molecular Genetics; Stepanets et al, 2001). As measured by the 16Q test (see below), standard production of 10 6 to 10 7 infectious units (IU)/ml was obtained with all virus strains.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of body and organ mass and immunohistochemistry of lymphoid tissues 2 weeks after hatching Table 4 11 Proliferative response to conA stimulation of splenocytes isolated from 2-week-old chickens inoculated in mid embryogenesis with RAV-1 or td daPR-C Table 6 12 Humoral immune response to B. abortus antigen of chickens inoculated in mid embryogenesis with RAV-1 or td daPR-C and repeatedly immunized in the period 2 to 8 weeks after hatching Table 7 Determination of the replicating virus in plasma. The presence of infectious virus in chicken plasma was determined by the complementation test with 16Q cells (quail cells harbouring the provirus of high-titre Bryan strain Rous sarcoma virus lacking the env gene) (Murphy, 1977), essentially as described previously (Stepanets et al, 2001). Briefly, chicken embryo fibroblasts were incubated with 100 ml chicken plasma, subcultured twice and co-cultivated with 16Q cells for 1 week.…”
Section: Methodsmentioning
confidence: 99%